Effects of cultivar and planting spacing on yield and yield components of garlic (Allium sativum L.) - Fakhar, Fahimeh; Biabani, Abbas; Zarei, Mehdi; Moghadam, Ali Nakhzari (Italian Journal of Agronomy, 2019)
Planting spacing is the systematic evaluation of the farm area or any growing surface for crop production. In order to study the effect of varying planting patterns in two garlic (Allium sativum L.) cultivars, an experiment was carried out as a factorial design based on randomised complete block design with three replications in the farm of Gonbad-e-Kavous University during 2016- 2017. The factors consisted of seven planting spacing (12.5×12.5, 15×15, 17.5×17.5, 20×20, 22.5×22.5, 25×25 and 27.5×27.5 cm) and two cultivars (Tarom and Hamedan). The fresh bulb yield, bulb weight, clove weight, clove number of bulb, plant height, bulb diameter, bulb length, clove diameter, skin number and stem length were recorded. Results showed that there were significant differences between both planting spaces and cultivars in all variables assessed. The highest bulb yield (19,014 kg ha–1) was recorded in Hamedan with the spacing 12.5×12.5 cm, while the lowest bulb yield (7572 kg ha–1) was detected in Tarom with the spacing 27.5×27.5 cm. The highest number of cloves was produced by Hamedan under the 27.5×27.5 cm arrangement. In addition, upon the correlation analysis between variables, the bulb weight showed the highest effect on garlic yield that bulb weight was negatively correlated with bulb yield (r= –0.60**). Generally, Cultivar Hamedan had a higher yield and yield components than Tarom and the spacing 12.5×12.5 cm had a higher yield than the other spacing.